AB0787 Evaluation of Longitudinal Association Between Changes in Facet Joints and Administration of Tumor Necrosis Factor Inhibitors in Ankylosing Spondylitis Using CT. (9th June 2015) - Chung, S.W.; Song, R.; Lee, Y.-A.; Hong, S.-J.; Yang, H.-I.; Lee, S.-H.
Abstract : Background: Ankylosing spondylitis (AS) is a chronic inflammatory arthropathy, which primarily affects the sacroiliac joints and axial skeleton. In AS, involvement of the facet joints results in both back pain, and limitation of spinal mobility. Involvement of facet joint in AS have been reported in several articles. Improvements in spinal mobility in AS after treatment with tumor necrosis factor (TNF) inhibitors have been reported. However, TNF inhibitors were reported to increase or to not inhibit structural damage progression in AS, as assessed using plain radiography. It seems logical that improvement in spinal mobility by TNF inhibitors would result from their effects on facet joint. Objectives: To study the effect of TNF inhibitors on progressive facet joint damage in AS patients. Methods: AS patients who were treated with TNF inhibitors and had 2 sets of spinal computed tomography (CT) scans, a median of 50.96±5.47 months apart, were included (n=25). Radiographic severity of facet joints was assessed by a new scoring system using CT. Total facet joints from C2-C3 to L5-S1 were scored: erosions 1, subchondral sclerosis 2, partial ankyloses 3, and total ankyloses 4. We compared the longitudinal effects of TNF inhibitors with non-TNF inhibitor treatment by scoring of facet joint of 25 AS patients who were not treated by TNF inhibitors. Results: The mean age were 30.9±6.7 years and no significant differences in gender distribution (male, 84% vs. 88%). The only significant difference between two groups was that TNF inhibitor treated group had longer disease duration (years, 4.15±4.02 vs. 2.13±1.73, p =0.001). Significant increases in CT score in the total spine and T-spine were observed in both groups at follow-up time points (Table 1 ). The rates of increase in CT score of the total spine were similar in both groups, whereas, the rates of increase in CT score of the T-spine was lower in the TNF inhibitor treated group than in the non-TNF group. However, the difference was not statistically significant ( p =0.387; Fig. 1 ). Conclusions: Treatment with TNF inhibitors did not prevent the radiographic progression of facet joints damage in AS patients References: Wilkinson M, Bywaters EG. Clinical features and course of ankylosing spondylitis; as seen in a follow-up of 222 hospital referred cases. Ann Rheum Dis. 1958;17:209-28. 2 Machado MA, Barbosa MM, Almeida AM et al. Treatment of ankylosing spondylitis with TNF blockers: a meta-analysis. Rheumatol Int. 2013;33:2199-213. Disclosure of Interest: None declared